Use of saturated green material in vaporic thermal atmosphere to absorb ions have negative impact - Ali Mahmood Karwi, Abbas; Mohammed Abdullah, Eman (International Journal of Engineering and Technology, 2018)
This design has been used to adsorb ions from industrial water of companies and factories. Our system has three integrated phases used to test efficiency of an unspecified number of residues of food as adsorbed materials. In this system, we adsorb copper and cobalt ions, these ions are available with high rates in Al Musayab thermal station, high concentration of these ions pose a threat to the health of the population. In general, the presence of these ions in the proportions set by the World Health Organization, namely, (1mg/L) are very useful for the com-pletion of the metabolic processes of the living cell, but a greater focus for this will lead to tremendous health risks. Testing processes a proved that there is an exact match between empirical and theoretical testes of (Freundlich and Langmuir) models. Through the mathematical analysis of the trial data under different thermal conditions, all testes proved that green algae powder is the best filtered material, because its high adsorption efficiency which equal to (77%) with Gips free energy equal to (-39 kJ/mol), followed by Pulp date powder has proven to be excellent efficiency (75%) with enthalpy equals to (-12 kJ/mol). In general, all food remnants have been selected to be test in our adsorp-tion system, this system has high capacity to adsorb various ionic roots of industrial water of Al-Musayab thermal station. All Adsorbents have thermal coefficient falls between one and zero (one<RL<0), this value represents the perfect choice of adsorption to be tested on this system. The total system cost is ($10000).Â Â